Effect of a comprehensive heart failure treatment program on left ventricular ejection fraction and six-minute walk distance in heart failure patients with reduced ejection fraction at Lampang Hospital - T, Boonyapiphat; K, Udol (Biomedical Sciences and Clinical Medicine, 2020)
Objectives Patients with chronic heart failure have excessively high mortality and readmission rates and a poor quality of life. This single group, pre-post intervention study aimed to evaluate the effects of a comprehensive heart failure treatment program on left ventricular ejection fraction (LVEF) and the six-minute walk distance in patients diagnosed with heart failure with reduced ejection fraction (HFrEF). Methods Patients with HFrEF participated in a comprehensive, on-going heart failure treatment program at Lampang Hospital. The program focuses on guideline-directed medical therapy (GDMT) for heart failure, cardiac rehabilita- tion, and health education for patients and caregivers regarding self-care and self-adjustment of diuretics. The program was managed by a multidisciplinary team comprised of cardiologists, heart failure nurses, pharmacists and physical therapists. LVEF was evaluated at baseline and at 6- and 9-month follow-ups. Six-minute walk distance was assessed at baseline and at 12±3 month follow-ups. Results Sixty-one HFrEF patients were included. After participation in the program, there was significant improve- ment in LVEF (mean LVEF 27% before participation vs. 47% at 6- and 9 month follow-ups, p<0.001) and six-minute walk distance (mean 313 m before participation vs. 357 m at 12±3 month follow-ups, p<0.001). Patients also reported improved quality of life and New York Heart Association functional class. Conclusions In patients with HFrEF, participation in a comprehensive heart failure treatment program may lead to improvement in LVEF and six-minute walk distance.